Opposing presynaptic roles of BDNF and ProBDNF in the regulation of persistent activity in the entorhinal cortex. Issue 1 (December 2016) - Gibon, Julien; Barker, Philip; Séguéla, Philippe
Abstract Background Sustained, persistent firing (PF) of cortical pyramidal neurons following a short depolarization is a crucial cellular mechanism required for spatial and working memory. Pyramidal neurons in the superficial and deep layers of the medial and lateral entorhinal cortex (EC) display this property of prolonged firing activity. Here, we focused on the regulation of this activity in EC neurons by mature brain derived neurotrophic factor (BDNF) and its precursor proBDNF. Results Using patch clamp electrophysiology in acute mouse cortical slices, we observed that BDNF facilitates cholinergic PF in pyramidal neurons in layer V of the medial EC. Inhibition of TrkB with K252a blocks the potentiating effect of BDNF whereas inhibition of p75NTR with function-blocking antibodies does not. By recording spontaneous excitatory post-synaptic currents (sEPSC), we find that BDNF acts pre-synaptically via TrkB to increase glutamate release whereas proBDNF acting via p75NTR acts to reduce it. MPEP abolished the facilitating effect of BDNF on PF, demonstrating that the metabotropic glutamate receptor mGluR5 plays a critical role in the BDNF effect. In contrast, paired pulse ratio and EPSC measurements indicated that proBDNF, via presynaptic p75NTR, is a negative regulator of glutamate release in the EC. Conclusions Taken together, our findings demonstrate that the BDNF/TrkB pathway facilitates persistent activity whereas the proBDNF/p75NTR pathway inhibits this mnemonic property of entorhinal pyramidal neurons.